Visual Reliance During Reactive Postural Control Following Unanticipated Perturbations in Chronic Ankle Instability and Ankle Sprain Copers - Min Jun Kim; Sehee Kim; Hye Young Ryu; Junyoung Kim; Sehoon Oh; J. Ty Hopkins; S. Jun Son (Medicine & Science in Sports & Exercise, 2026)
Purpose: To investigate the effect of visual disruption on reactive postural control during unanticipated medial and lateral perturbations in individuals with chronic ankle instability (CAI), ankle sprain copers, and healthy controls. Methods: Forty-five participants (15 per group) performed single-leg stance trials on a robotic force-plate system that delivered unanticipated medial and lateral perturbations under eyes-open and stroboscopic vision conditions. The primary outcome was the resultant vector time to stabilization (RVTTS). A two-way mixed-model ANOVA examined group × visual condition interactions, and Romberg ratios (stroboscopic vision/eyes-open) quantified visual reliance. Results: Significant group × visual condition interactions were observed for RVTTS during medial ( F (2,42) = 7.12, P = 0.002) and lateral ( F (2,42) = 6.14, P = 0.005) perturbations. Under the stroboscopic vision condition, CAI and ankle sprain coper groups demonstrated significantly longer RVTTS than the healthy control group ( P < 0.001–0.004), whereas no group differences were observed under the eyes-open condition ( P = 0.051–0.612). No significant differences were found between the CAI and ankle sprain coper groups ( P = 0.134–0.359). Additionally, the CAI and ankle sprain coper groups showed significantly higher Romberg ratios than the healthy control group for medial ( P = 0.002–0.007) and lateral ( P = 0.007–0.035) perturbations. Conclusions: These findings provide novel evidence of increased visual reliance during reactive postural control in individuals with a history of lateral ankle sprain. Notably, ankle sprain copers, traditionally regarded as functionally recovered, exhibited visual reliance patterns indistinguishable from CAI patients, which may reflect latent sensorimotor dysfunction detectable only when visual disruption and unanticipated perturbations are simultaneously imposed. Incorporating visual disruption into reactive balance assessments may enhance detection of latent sensorimotor deficits following ankle sprain.